Impacto de los microcréditos productivos entregados a los migrantes y sus familias por la cooperativa KW perteneciente a la agencia Guamaní en el periodo fiscal 2022 -2023 - Sisa Villa, Ángel Cristóbal (2025)
The main objective of this research was to analyze the impact of productive micro-credits provided to migrants and their families in Ecuador through the KW cooperative at the Guamaní agency. A survey was conducted, revealing that these types of micro-credits contribute to improving the quality of life of the debtors. The research was carried out through a qualitative-quantitative methodological structure, and the expected result was obtained. The technique employed was documentary observation, and the method used for data collection was a survey. Due to its adaptability to this type of process, the survey was employed as an evaluation tool for individuals anonymously, obtaining both qualitative and quantitative data for this research. This was done to create a tool that provides the KW cooperative with a control mechanism within the micro-credit segment and to monitor the process of using the funds disbursed as micro-credits. Finally, the financial entity experienced an increase in delinquency in this micro-credit segment, resulting in a reduction in its liquidity and solvency. Meanwhile, the financial situation of the primary debtors directly impacts the guarantors, who are responsible for assuming the financial obligations if the debtors fail to meet their commitments. Therefore, the financial entity must refinance and restructure the micro-credit processes to reduce credit risk and improve its financial indicators.